Las plantas exogenas en la taxonomia mixteca (Mexico) - Katz, E. (1998)
After the Spanish conquest of Mexico, many plants were introduced in the Mixtec Highlands as in the whole country. In this article, the names given to introduced plants in local Spanish and Mixtec are analysed from an ethnoscience point of view: How do new plants fit into indigenous classification? What do they reveal about social representations?